The transcriptional elongation factor CTR9 demarcates PRC2-mediated H3K27me3 domains by altering PRC2 subtype equilibrium. Issue 4 (7th February 2022) - Chan, Ngai Ting; Huang, Junfeng; Ma, Gui; Zeng, Hao; Donahue, Kristine; Wang, Yidan; Li, Lingjun; Xu, Wei
Abstract: CTR9 is the scaffold subunit in polymerase-associated factor complex (PAFc), a multifunctional complex employed in multiple steps of RNA Polymerase II (RNAPII)-mediated transcription. CTR9/PAFc is well known as an evolutionarily conserved elongation factor that regulates gene activation via coupling with histone modifications enzymes. However, little is known about its function to restrain repressive histone markers. Using inducible and stable CTR9 knockdown breast cancer cell lines, we discovered that the H3K27me3 levels are strictly controlled by CTR9. Quantitative profiling of histone modifications revealed a striking increase of H3K27me3 levels upon loss of CTR9. Moreover, loss of CTR9 leads to genome-wide expansion of H3K27me3, as well as increased recruitment of PRC2 on chromatin, which can be reversed by CTR9 restoration. Further, CTR9 depletion triggers a PRC2 subtype switch from the less active PRC2.2, to the more active PRC2.1 with higher methyltransferase activity. As a consequence, CTR9 depletion generates vulnerability that renders breast cancer cells hypersensitive to PRC2 inhibitors. Our findings that CTR9 demarcates PRC2-mediated H3K27me3 levels and genomic distribution provide a unique mechanism that explains the transition from transcriptionally active chromatin states to repressive chromatin states and sheds light on the biological functions of CTR9 in development and cancer.